Association between physical activity and quality of life in a sample of Malaysian obese children - Sharifah Wajihah Wafa, Syed Saadun Tarek Wafa; Talib, R; Hamzaid, N (2014)
Purpose: This cross-sectional study aimed to investigate the relationship between health quality of life, physical activity, and weight status in children aged 7–11 years old. Study participants Participants (80 boys and 79 girls) completed a validated quality of life (QOL) inventory and wore an accelerometer to objectively measure physical activity for 1 week. Methods: WHO (2007) standardized growth charts were used to categorize participants as obese (SD >+ 2 SD) and normal weight status (SD >− 2 SD z <+ 1 SD) while accelerometer data was used to categorize participants as meeting or not meeting the recommended guidelines for physical activity. Results: Psychosocial and total QOL (all P < 0.05) were significantly lowered for obese when compared to normal weight participants. Less physically active children, irrespective of weight status, had significantly lower psychosocial and total QOL (all P < 0.05). Conclusion: Physical activity promotion in obese children may have additional benefits to weight management that include improving QOL.